CITY BRANDING SEBAGAI STRATEGI PENGEMBANGAN PARIWISATA DITINJAU DARI ASPEK HUKUM MEREK (STUDI KASUS CITY BRANDING DAERAH ISTIMEWA YOGYAKARTA SEBAGAI DAERAH TUJUAN WISATA UNGGULAN DI INDONESIA) - Aditya Yuli (Fakultas Hukum Universitas Wahid Hasyim, 2011)
One of the tourism object that have special attraction is Yogyakarta, Yogyakarta istypically able to deliver persistence of Sultanate Ngayogyakarta customs anduniqueness of Javanese culture that is able to attract public attention, so it makethis city as a leading cultural tourism destination in Indonesia and could boost thedevelopment of small and medium industries with the growth of creativeindustries in it. By carrying the slogan “Never Ending Asia”, Yogyakarta couldbecome a thriving tourism business.Law No. 15 of 2001 on Marks have not set about city branding as one of theclasses in the right brand the ca be registered to the General Directorate ofIntellectual Property Right. This can be seen from the absence of definition ingeneral terms or any information on the explanation of the Act which states citybranding. Jogja: Never Ending Asia, only a brand image in the province of DIYand do not register at the Directorate Genera of Property Rights as the concept ofbrand in the Law No. 15 of 2001 on Branding.Viewing the conditions of tourism Indonesia and Yogyakarta that is very strategic,advice can be given for the advancement of tourism in Indonesia is to reinforce thedefinition of City Branding itself, namely by making changes to the Law No. 15 of2001.Keyword: City Branding, tourism, Brand